Effect of chiral photosensitive liquid crystalline dopants on the performance of organic solar cells. (February 2015) - Iwan, Agnieszka; Boharewicz, Bartosz; Tazbir, Igor; Hamplová, Věra; Bubnov, Alexej
Highlights: We applied chiral photosensitive liquid crystalline materials as additives. We constructed polymer devices with LC compounds. We analyse photovoltaic, electrical, optical and thermal properties in the level of kind and amount of LC. The J–V effects depend on the chemical structure of LC material, viscosity of PEDOT:PSS and temperature applied. Abstract: In order to design a new type of an organic solar cell device and to contribute for its performance optimization, i.e. transport and optical properties, a composite organic solar cell have been designed. It has been fabricated in two modifications from poly(3-hexylthiophene) and [6, 6]-phenyl C61 -butyric acid methyl ester mixtures (P3HT:PCBM) and two chiral photosensitive liquid crystalline (PCLC) materials used as additives. Doping of the P3HT:PCBM solar cell by a specific PCLCs led to a distinct adjustment (increase or decrease) of power conversion efficiency in comparison to that of an undoped cell and it is also strongly depends on the viscosity of the PEDOT:PSS used. In order to control the properties of the resulting composite P3HT:PCBM solar cells doped by PCLCs, the photovoltaic and impedance spectroscopy studies have been done for active layers annealed at different temperatures. Differential scanning calorimetry (DSC) in combination with polarized optical microscopy (POM) has been used to examine the morphology of an active layer. Thermal annealing of the sample within a mesophase temperature range can remove defects, optimize the morphology of the active layer, and hence might be responsible for the increase of photocurrent and cell efficiency.